PENGARUH INDUKSI MEDAN RADIO FREQENCY (RF) PADA DIPOL-DIPOL MOLEKUL AIR - Firdausi, Ketut Sofjan; Kamil, Ahmad; Azam, Muchammad (JURNAL SAINS DAN MATEMATIKA, 2009)
ABSTRACT-The non-linear optical property of rotary power of light polarization in water has been develop using the Radio-Freguency field (RF-Field). The RF-Field used in the experiment is produced by RF generator, and it supplies the frequency in the range betwen 6,04 to 14,56 MHz which then applies to the samples. The source of light with 632,8 nm-wavelength and 532 nm-wavelength are used to observe the change of range polarization of the light after it passes througt the samples. Three modes of the direction of the electric field of light are chosen 0o (E//) (E of light is parallel to E of RF-Field), and 90o (E ) (E of light is perpendicular to E of the RF-Field) in order to determinate the optimal change of the angle of the polarization β. The values of β is measured as a function of RF-Field, , where ωRF is the angular frequency of RF-Field and BRF is the magnitude of magnetic field measured in the center of the coil which is assumed to be homogeny in the circumstances of the samples. The results of the experiment show that the degrees of change of the polarization direction, η is largest at the E3 mode. It shows also that at small wavelength of light we obtain the larger η, which is indicated the higher frequency of liglt will more induce the dipoles of molecules of the samples. Keywords: non- linear optics, polarization angle, rotary power